Artificial Intelligence Technology Adoption Decision-Making Process in MSMEs Marketing Practices - Mustika, Hexadilla; Setiaman, Agus; Octavianti, Meria (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
Artificial intelligence (AI) is a technology that transforms various aspects of life, including business marketing practices. This study aims to describe the decision-making process in adopting AI among MSMEs in DKI Jakarta and Greater Bandung. A descriptive quantitative method was used with descriptive analysis and cross-tabulation. A total of 119 MSME respondents who are digitalized and familiar with AI were analyzed to map the AI adoption process. The results show that most respondents have adopted AI, especially micro-businesses in the culinary sector. Respondents demonstrated basic knowledge of AI, along with personal characteristics and communication habits that support adoption. AI is perceived to offer relative advantages, compatibility with values and needs, ease of trial, and observable results. However, some respondents still find AI difficult to use. Improving AI training, digitalization efforts, and supportive policy-making are needed to strengthen the digital ecosystem for MSMEs.